Clinical relevance of serum antibodies to GD1b in immune‐mediated neuropathies. Issue 4 (12th September 2018) - Taams, Noor E.; Notermans, Nicolette C.; Fokkink, Willem‐Jan R.; Tio‐Gillen, Anne P.; Huizinga, Ruth; Schreurs, Marco W. J.; Jacobs, Bart C.
Abstract : Antibodies to the ganglioside GD1b have been reported in various forms of immune‐mediated neuropathy, but their clinical relevance for diagnosis and prognosis is unknown. We investigated the prevalence of anti‐GD1b antibodies in acute and chronic immune‐mediated neuropathies, and the clinical presentation and outcome in Guillain‐Barré syndrome (GBS) and Miller Fisher‐GBS overlap syndrome (MF‐GBS). Anti‐GD1b, anti‐GM1 and anti‐GQ1b antibodies were tested in serum of patients with GBS ( N = 165), Miller Fisher syndrome ( N = 10), MF‐GBS ( N = 28), monoclonal gammopathy of unknown significance neuropathy (MGUS; N = 101), chronic inflammatory demyelinating polyneuropathy ( N = 29), paraneoplastic syndrome with anti‐Hu‐associated neuropathy (PNS; N = 11), other auto‐immune diseases (AID; N = 60), and healthy controls (HC; N = 60). All samples were tested by enzyme‐linked immunosorbent assay according to the Inflammatory Neuropathy Cause and Treatment protocol. IgM anti‐GD1b antibodies were found in GBS ( N = 4; 2.4%), MGUS ( N = 3; 3.0%), and PNS patients ( N = 1; 9.1%). IgG anti‐GD1b antibodies were found in GBS ( N = 20; 12.1%) and MF‐GBS ( N = 4; 14.3%) patients, but not in the AID and HC group. In the combined group of MF‐GBS and GBS patients ((MF‐)GBS), 14/36 (38.9%) patients with IgG anti‐GD1b antibodies also had IgG anti‐GM1 antibodies, and IgG anti‐GD1b and IgG anti‐GQ1b antibodies were found in 3/29 (10.3%) patients. Patients with (MF‐)GBS and anti‐GD1b without anti‐GM1 antibodies did not differ regarding sensory disturbances or disease severity but recovered faster regarding the ability to walk independently compared with patients without anti‐GD1b antibodies ( P = 0.031) and with patients with both anti‐GD1b and anti‐GM1 antibodies ( P = 0.034). In conclusion, testing for anti‐GD1b antibodies may identify a specific group of immune‐mediated neuropathies and (MF‐)GBS patients with only anti‐GD1b antibodies tend to recover faster.